2006
DOI: 10.1016/j.ymthe.2006.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Armed Oncolytic and Immunologic Therapy for Cancer with JX-594, a Targeted Poxvirus Expressing GM-CSF

Abstract: Targeted oncolytic viruses and immunostimulatory therapeutics are being developed as novel cancer treatment platforms. These approaches can be combined through the expression of immunostimulatory cytokines from targeted viruses, including adenoviruses and herpesviruses. Although intratumoral injection of such viruses has been associated with tumor growth inhibition, eradication of distant metastases was not reported. The major limitations for this approach to date have been (1) inefficient intravenous virus de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
227
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(240 citation statements)
references
References 40 publications
0
227
0
1
Order By: Relevance
“…15); this virus was designated JX-963. Because human GM-CSF is not active in rodents but is active in rabbits (16), and in order to assess the activity against much larger primary tumors that reproducibly metastasize, JX-963 was used in a rabbit model with primary (VX2) liver tumors and lung metastases (17). At the time of dosing, multiple 1-to 2-mm tumor metastases were already evident on histopathology of the lungs of control rabbits.…”
Section: Jx-963 (Vvdd-gm-csf) Final Product Engineering and Evaluatiomentioning
confidence: 99%
“…15); this virus was designated JX-963. Because human GM-CSF is not active in rodents but is active in rabbits (16), and in order to assess the activity against much larger primary tumors that reproducibly metastasize, JX-963 was used in a rabbit model with primary (VX2) liver tumors and lung metastases (17). At the time of dosing, multiple 1-to 2-mm tumor metastases were already evident on histopathology of the lungs of control rabbits.…”
Section: Jx-963 (Vvdd-gm-csf) Final Product Engineering and Evaluatiomentioning
confidence: 99%
“…18) expressed from vaccinia virus or GM-CSF (19) expressed from herpes simplex virus] has shown great promise in clinical trials. In addition, preclinical reports of other viruses modified to express cytokines were able to confer an increase in their therapeutic efficacy in several tumor models (20)(21)(22)(23)(24)(25)(26)(27). In this regard, we developed several NDV vectors carrying GM-CSF, tumor necrosis factor (TNF)-a, IFN-g, or IL-2 and tested them for increased therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…This study documented tumor-specific virus replication and gene expression, GM-CSF detection, and tumor-infiltrating cytotoxic T-lymphocytes. 59 The effect of JX-594 on the tumor-associated vasculature was tested; the results showed a significant regression in the tumor-associated vasculature in xenograft models as well as in patients. This study demonstrated that a biologic agent can be used for infection and selective replication in endothelial cells.…”
Section: Wyeth Strainsmentioning
confidence: 99%